ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMANFAATAN DAN PENGGUNAAN SISTEM INFORMASI (Studi pada Pemerintah Daerah Kabupaten Bantul) - Muhammad Erwin Prasetiya; Rohmad Yuliantoro (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2012)
The main purpose of this research is to examine the inflence of performance expactation of business and social factor, factor the suitability of assigments of interest utilizing information system and test the influence of conditions that facilitate user and system utilization onformation of interest in the use of information system has brought a very fundamental changes for the organization whether private or public organizations.                Therefore, information system become very important in determining competitiveness and the ability of the company to improve business performance in the future. Population in this research in Goverment employees Bantul Regency. The technique to gather sample is judgmental technique (purposive).                Data collected by using a questionnaire. 146 questionnaire returned from 200 sent and only 115 that can be processed. Data analysis was done using regression technique. The yhpothesis of this research was tested by using a two-equation of regression.                The results of this research show thaat performance expectations, expectations of business, social factors, and the suitability of the tasks affect the interest of the utilization of information systems. The conditions that facilitate user do not affect the use of the system of information and interest of the utilization of information systems affect the use of system information.